SIDE STREAMING ON BANK FINANCING: CAUSES, FORMS, IMPACT AND PREVENTION - Budiono, I Nyoman; Muhammadun, Muzdalifah; S, Andi Bahri; Sari, Nur Aisah; Husna, Asmaul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research is entitled "Side Streaming on Conventional Bank Credit and Islamic Bank Financing. This study aims to determine the causes of side streaming, the forms of side streaming, the impact of side streaming, as well as efforts to prevent and resolve side streaming in conventional bank credit and Islamic bank financing. The methodology used is a qualitative descriptive method using primary data and secondary data. The results of the study show that side streaming can occur due to several reasons, namely: weaknesses in SOPs, lack of anticipation from the Financing Committee/Credit Committee, over-financing, there is an intention on the part of the customer to do side streaming, errors on the part of the account officer or officer who performs the financing analysis/credit analysis. The forms of side streaming, namely: working capital financing is used for consumptive purposes, working capital side streaming is for investment needs, working capital side streaming is used to finance working capital for new businesses and working capital side streaming is for digging holes to close holes. Side streaming can have a negative impact on customers and banks, including: the business being financed does not develop, side streaming has the potential to cause financing problems. Efforts to prevent side streaming can be done by providing strict SOPs to prevent side streaming, taking preventive measures from the credit/financing committee, carefully calculating credit or financing needs, carrying out checks that are more careful, account officers are more careful in conducting credit/financing analysis. To resolve the occurrence of side streaming, the following steps can be taken: Conducting coaching to customers, requesting repayment of financing to customers, restructuring financing / credit and carrying out liquidation of guarantees provided